2021
DOI: 10.1155/2021/9934942
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Biogas Technology Adoption in Rural Households of Aleta Wondo District, Sidama Zone, Southern Ethiopia

Abstract: Biogas is environmentally sound and economically viable, clean, and renewable energy source. Despite its numerous benefits and dissemination efforts, the adoption of biogas technology has been low. The objective of this study was to assess factors determining adoption of biogas technology as an alternative energy source at household level in Aleta Wondo district, southern Ethiopia. A multistage sampling technique was employed to select sample households. A total of 148 sample households, 51 biogas technology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This indicates that family size does not affect the households efficient stove use. However, studies conducted by Bekere and Megerssa [44], Geddafa, Melka, and Sime [45] and Woubishet [46] indicated that sex of household head and family size are important determinants in adopting Mirt stoves and biogas technology. In fact, the findings of Bekere and Megerssa [44], Geddafa, Melka, and Sime [45], in particular, are based on the adoption of biogas technology and Mirt stoves in rural areas, but not in informal settlements.…”
Section: Factors Affecting Energy-efficient Stove Use: Descriptive An...mentioning
confidence: 99%
“…This indicates that family size does not affect the households efficient stove use. However, studies conducted by Bekere and Megerssa [44], Geddafa, Melka, and Sime [45] and Woubishet [46] indicated that sex of household head and family size are important determinants in adopting Mirt stoves and biogas technology. In fact, the findings of Bekere and Megerssa [44], Geddafa, Melka, and Sime [45], in particular, are based on the adoption of biogas technology and Mirt stoves in rural areas, but not in informal settlements.…”
Section: Factors Affecting Energy-efficient Stove Use: Descriptive An...mentioning
confidence: 99%